Comportamento dos processos intra-organizacionais de aprendizagem tecnológica frente a uma mudança de estrutura de propriedade: o caso da TermoMacaé - PETROBRÁS - Pereira, José Antônio Maciel (2008)
This academic work describes the interfirm technological learning processes behavior at a thermo plant throughout the years 2001 till 2007. Its former ownership structure was composed by two foreigners companies. This structure was changed by the acquisition of the company control by a Brazilian state owned company on April 2006. The company is a Natural Gas Fired Power Plant placed at Macaé City, at Rio de Janeiro State, Brazil generating electric power right to National Integrated System (SIN). The goal of this research is verify how the technological knowledge had been acquired by the firm and how it had been spread out throughout the organization before and after the change of the ownership structure. The taxonomy applied to determining of ownership structure take in account three parameters: type, specific characteristic and the ownership structure itself. Technological Learning Interfirm Processes have been examined from a model of systemic approach that establishes four key characteristics: ¿variety, intensity, functioning and interaction¿. During 2001 until 2006, till the change of owner structure, the firm developed its own learning processes in its own operational routines. The main learning processes have been identified from empirical evidences. It has been adopted the cut line at year of 2006 for the comparison among the technological learning processes behavior, when the change of ownership structure took place. The data capture occurred within April and August 2007 covering since 2001. Verified the behavior of these learning processes before and after the ownership structure changed from private property to state owned property. The conclusion of this case study suggests that interfirm processes of technological learning identified by the research had their dynamical behavior promptly affected by a change from private to ownerstate ownership structure, exposing the company to a poor performance in its industry, due to the lack of 51% of the technological intrafirm learning processes and reduction of the acquisition of new technical knowledge and its conversion throughout the organization.